Are Current Tax and Spending Regimes Sustainable in Developing Asia? - Sang-Hyop Lee; Andrew Mason (Asian Development Bank (ADB), 2014)
Changes in population age structure matter for public finances because the beneficiaries of public programs are primarily children and the elderly. This paper projects government spending on education, health care, and social protection in developing Asia up to 2050 using the National Transfer Accounts data set, United Nations' population projections, and other long-range projections for real gross domestic product (GDP) to estimate likely fiscal burdens as a result of demographic changes and economic growth. The share of GDP devoted to public spending on health care and social protection will increase as demographic change and economic growth are mutually reinforcing. On the contrary, the share devoted to public spending on education will decline in Asia and the Pacific as a decline in fertility and the share of the school-age population dominates the increase in per capita benefits. The magnitude and the pattern by program, however, vary substantially as demographic change, growth, and the current level of public spending are quite different across economies. Social spending in the Republic of Korea; the People's Republic of China; and Taipei,China is projected to more than double as a share of GDP by 2050, while it will be more modest in other areas of Asia and the Pacific.
hdl:11540/4210
Keywords: H51; H53; H68; J11; 330; fiscal projection; population aging; social welfare expenditure; Haushaltsplanung; Alternde Bevölkerung; Öffentliche Sozialausgaben; Asiatisch-pazifischer Raum